2019
DOI: 10.1371/journal.pone.0217429
|View full text |Cite
|
Sign up to set email alerts
|

Serum apoptotic marker M30 is positively correlated with early diastolic dysfunction in adolescent obesity

Abstract: Purpose Obesity in adolescence has been shown to be related to cardiac geometric and functional changes. Cardiac dysfunction in adults with obesity could be attributed to chronic low-grade inflammation, apoptosis of cardiomyocyte, and glucose metabolic disorder. The aforementioned association in adolescents with obesity have never been well studied. Our aim was to determine the types of cardiac dysfunction in adolescents with obesity and survey the association between cardiac dysfunction and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Apoptosis of cardiomyocytes is associated with both the aging process and chronic cardiac overload [50] and plays a substantial role in altering cardiac geometry and progressively deteriorating myocardial function, potentially leading to chronic cardiomyopathy and advanced heart failure [51]. A recent study reported that CK18 (M30) level was highly correlated to left ventricular (LV) diastolic dysfunction in adolescents with obesity [52], although CK18 (M65) had not been investigated. In addition, another study determined the relationship between the development of LV remodeling and CK18 (M30) but not CK18 (M65) in patients with anterior ST-segment elevation myocardial infarction [53].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of cardiomyocytes is associated with both the aging process and chronic cardiac overload [50] and plays a substantial role in altering cardiac geometry and progressively deteriorating myocardial function, potentially leading to chronic cardiomyopathy and advanced heart failure [51]. A recent study reported that CK18 (M30) level was highly correlated to left ventricular (LV) diastolic dysfunction in adolescents with obesity [52], although CK18 (M65) had not been investigated. In addition, another study determined the relationship between the development of LV remodeling and CK18 (M30) but not CK18 (M65) in patients with anterior ST-segment elevation myocardial infarction [53].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the different change of LVFP between races may be caused by disproportionate changes in mitral annular eʹ velocity and mitral E velocity between CH and CA subjects following exercise. As previously reported, LV diastolic function and LVFP were associated with HR [39], hemodynamics [5,28,29], exercise capacity [17,24], LV deformation [33,43,45] and BMI [35,47]. We also investigated whether baseline HR, BP, aerobic capacity, DWS, and BMI might produce different influences on ΔE/eʹ between races.…”
Section: Discussionmentioning
confidence: 59%
“…K18 has been proposed as a biomarker for a range of liver conditions including acute liver failure and chronic liver diseases such as viral hepatitis, non-alcoholic fatty liver disease and liver cancer (Ku et al 2016). While an advantage of K18 as a biomarker is that it is an early marker of apoptosis/necrosis; a disadvantage is that it is also a biomarker for dysfunction in tissues other than the liver including the lung (Fu et al 2019;Levy et al 2019;Molnar et al 2019;Tajima et al 2019) (Yang et al 2019). Thus, a panel of 3 or 7 biomarkers may be advantageous over a single biomarker.…”
Section: Discussionmentioning
confidence: 99%